Flat, cheap, and under control [electrochemical mechanical planarization]. - Brown, A.S.
This paper describes Applied Material's wafer polishing technology, called electrochemical mechanical planarization (ECMP). ECMP is the answer to the problems of electropolishing and chemical mechanical planarization (CMP) of the chip-making process: manufacturing faster, more powerful chips without obliterating their vanishing fine and increasingly fragile features. It is designed to remove excess copper from the top of a newly formed layer of wiring on a chip without damaging the fragile insulation material, called a dielectric, beneath it. ECMP combines aspects of two other technologies, chemical mechanical planarization (CMP) and electropolishing.
Keywords: Chemical mechanical planarization; Chip-making process; Electrochemical mechanical planarization; Electropolishing; Fragile insulation material; Wafer polishing technology